Recurrent Acute Necrotizing Encephalopathy with underlying RANBP2 mutation. (5th December 2022) - Angappan, Dhanalakshmi; Hollen, Christopher
Abstract : Objective: N/A. Background: Acute necrotizing encephalopathy (ANE) is a rapidly progressive encephalopathy that can occur in otherwise healthy children after common viral infections such as influenza and parainfluenza. Most ANE is sporadic and nonrecurrent (isolated ANE). We report a case of recurrent acute necrotizing encephalitis in a boy with an identified RANBP2 mutation, which is known to account for the majority of recurrent ANE cases. Design/Methods: CASE REPORT Our patient is a 13-year-old boy with no significant medical or developmental history and no family history of neurodevelopmental disorders.He had his first episode at 15 months of agewhich manifested as irritability, non-responsiveness and was diagnosed as acute disseminated encephalomyelitis (ADEM) and subsequently had 4 additional episodes of ANE at ages 4, 4.5, 5, and 10. After his third episode, testing for RANBP2 was performed and found to be positive. His typical presentation includes fever, staring spells, nystagmus and altered sensorium during these episodes typically within 24 hours of febrile-illness. He has had multiple triggering viral infections identified including adenovirus, influenza A and parainfluenza. Ultimately his ANE episodes were managed with iv pulse steroid therapy and IVIG.With treatment he has had a slow but nearcomplete recovery, including radiological resolution. He does have mild cognitive impairment and learning difficulties which have persisted. Results: N/A. Conclusions: This patient has had numerous episodes of ANE triggered by infection that have responded well to acute management without prophylactic immunomodulation. This is, to our knowledge, themost non-fatal recurrences that have been reported with this condition. Our case suggests that multiple relapses are possible in patients with ANE and early diagnosis and treatment of the episodic encephalopathy would result in improved outcomes. Our case raises the consideration of prophylactic immunotherapy but also demonstrates a relatively positive outcome with a watchful management approach. Keywords: acute necrotizing encephalopathy.